L’A.I. uguale/quasi-uguale all’intelligenza umana? Considerazioni sull’esempio della Decima Sinfonia di Beethoven - Busacchi, Vinicio (B@belonline, 2024)
This article focuses on the question concerning the relationship between artificial and human intelligence. The reflection is intertwined with the controversy relating to an alleged Beethoven’s tenth symphony recently completed by A.I. This would demonstrate not only the advanced level of artificial intelligence but its creative capacity. Dealing with this case via Emilio Betti’s hermeneutical perspective, the author unmasks the substantial narrative deception of this argument.